Assessing the socio-economic impact of youth engagement in agricultural enterprise for employment creation and poverty alleviation - Ongama Giwu; Lelethu Mdoda; Samuel S. Ntlanga (Cogent Social Sciences)
In South Africa, high unemployment rates persist, particularly among the country's youth and rural residents, exacerbating socio-economic challenges such as food insecurity and poverty. Despite government initiatives aimed at promoting entrepreneurship to combat youth joblessness, participation in agriculture remains low due to negative perceptions regarding the field's status and potential earnings. This study examines the socio-economic impact of youth involvement in agriculture, with a focus on job creation and poverty alleviation in the Umzimvubu Local Municipality, Eastern Cape Province. Data was collected from 210 youth using a stratified random sampling method, and analysis was conducted using logit regression and propensity score matching techniques. The results indicate that youth engage in agriculture to enhance employment opportunities and household food security, making significant contributions to farm income and poverty reduction. Recommendations include government interventions such as mentorship programs and skills training to support youth in agricultural enterprises. These findings highlight the pressing need for targeted strategies to address youth poverty and vulnerability in South Africa.